Cassia tora extract alleviates Aβ1–42 aggregation processes in vitro and protects against aluminium-induced neurodegeneration in rats - Sunil K. Ravi (2020)
© 2020 Royal Pharmaceutical Society Objectives: To examine the ability of Cassia tora extract to produce, in vitro and in vivo, beneficial effects with respect to events occurring during Alzheimer's disease. Methods: Previously characterised methanol extract of C. tora was tested for its ability to lessen Aβ42 aggregation processes in vitro and to alleviate aluminium-induced impairments in vivo in rats. Key findings: Cassia tora extract prevents the aggregation of monomeric, oligomeric and fibrillary Aβ1–42 in vitro. Moreover, the daily ingestion of 100 and 400 milligrams of the extract per kilogram of body weight for 60 days ameliorates the neurobehavioral and cognitive abilities of aluminium-treated rats in vivo. Importantly, treatments with the extract trigger a significant recovery of antioxidant enzymes function, a diminution of lipid peroxidation and acetylcholinesterase activity, a decrease of pro-inflammatory cytokines expression and an increase of brain-derived neurotrophic factor levels in both the hippocampus and the frontal cortex. Finally, we evidence that the extract is able to ameliorate the aluminium-dependent loss of neuronal integrity in the CA1 and CA3 regions of the hippocampus. Conclusions: Altogether, our results reveal that methanol extract of C. tora is able to prevent typical AD-related events and therefore stands as a promising mild and natural anti-AD multitarget compound.